2022
DOI: 10.3390/reactions3040036
|View full text |Cite
|
Sign up to set email alerts
|

Greener and Efficient Epoxidation of 1,5-Hexadiene with tert-Butyl Hydroperoxide (TBHP) as an Oxidising Reagent in the Presence of Polybenzimidazole Supported Mo(VI) Catalyst

Abstract: Alkene epoxidation with TBHP as an oxidising reagent using heterogeneous Mo(VI) catalyst is an environmentally friendly process since it eliminates acid waste and chlorinated by-products often associated with the conventional industrial method that uses stoichiometric peracid such as peracetic acid and m-chloroperbenzoic acid. Polybenzimidazole supported Mo(VI) complex, i.e., PBI.Mo has been successfully prepared, characterised and assessed for the epoxidation of 1,5-hexadiene in the presence of tert-butyl hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(39 reference statements)
3
3
0
Order By: Relevance
“…9 Ambroziak et al 34 mentioned that increasing the feed molar ratio lowers the TBHP concentration to such an extent that it slows down the conversion of TBHP into epoxide. A similar feed molar ratio effect was reported in my previous published results; 35 it has been demonstrated that there was no significant difference in the rate of epoxidation when the feed molar ratio of 1,5-hexadiene to TBHP was increased from 2.5 : 1 to 10 : 1.…”
Section: Reaction Chemistry and Engineering Papersupporting
confidence: 88%
“…9 Ambroziak et al 34 mentioned that increasing the feed molar ratio lowers the TBHP concentration to such an extent that it slows down the conversion of TBHP into epoxide. A similar feed molar ratio effect was reported in my previous published results; 35 it has been demonstrated that there was no significant difference in the rate of epoxidation when the feed molar ratio of 1,5-hexadiene to TBHP was increased from 2.5 : 1 to 10 : 1.…”
Section: Reaction Chemistry and Engineering Papersupporting
confidence: 88%
“…Such a drawback exists with almost all chemical reactions regardless of sector however, outlining the weighting of the benefits of using a polymer structure as a heterogeneous catalyst can possess over any negative aspects. Similar studies investigating the preparation of epoxides using a polybenzimidazolesupported Mo(VI) catalyst [200,201] produced similar results. Whilst the alkene being epoxidized varied between the studies, the findings illustrated that a polymer-based catalyst structure (in this case polybenzimidazole) is active in these reactions, and exhibits particularly high activity under reaction-specific optimized conditions.…”
Section: Polymer-supported Catalystssupporting
confidence: 67%
“…However, such a drawback exists for almost all chemical reactions regardless of sector, outlining the importance of weighing the benefits of using a polymer structure as a heterogeneous catalyst over any negative aspects. Similar studies investigating the preparation of epoxides using a polybenzimidazole-supported Mo(VI) catalyst [254,255] produced similar results. Whilst the alkene being epoxidised varied between the studies, the findings illustrated that a polymer-based catalyst structure (in this case, polybenzimidazole) is active in these reactions, and it exhibits particularly high activity under reaction-specific optimised conditions.…”
Section: Polymer-supported Catalystssupporting
confidence: 66%